Meister Eckhart in Melk - Löser, Freimut,L Ser, Freimut,Leoser, Freimut,Loser, Freimut (De Gruyter, 1999)
The present study deals with the reception of the works of Meister Eckhart during the first half of the 15th century at the Benedictine monastary of Melk (Austria). Eckhart's work is to be found there in manuscripts of the laybrother Lienhart Peuger only. A detailed description of these manuscripts (also introducing some hitherto unknown sermons by Eckhart) is preceded by a more general discussion of the role of the laybrothers during the Benedictine 'Melk Reform'. The treatise »Von der sel wirdichait vnd aigenschafft« (»On the Nobility and Character of the Soul«), which is transmitted in one of Peuger's manuscripts, was formerly believed to be a work of Eckhart himself; as such it was edited by Franz Pfeiffer. The present study and the new edition set out to prove that the treatise was compiled by Peuger, and list all the Eckhartian materials he used.
Description based on publisher supplied metadata and other sources
Keywords: Eckhart; Peuger; Lienhart; Rezeption; Handschrift